Ferroptosis driven by radical oxidation of n-6 polyunsaturated fatty acids mediates acetaminophen-induced acute liver failure - Yamada, Naoya; Karasawa, Tadayoshi; Kimura, Hiroaki; Watanabe, Sachiko; Komada, Takanori; Kamata, Ryo; Sampilvanjil, Ariunaa; Ito, Junya; Nakagawa, Kiyotaka; Kuwata, Hiroshi; Hara, Shuntaro; Mizuta, Koichi; et al. (Cell death & disease, 2020)
Acetaminophen (APAP) overdose is a common cause of drug-induced acute liver failure. Although hepatocyte cell death is considered to be the critical event in APAP-induced hepatotoxicity, the underlying mechanism remains unclear. Ferroptosis is a newly discovered type of cell death that is caused by a loss of cellular redox homeostasis. As glutathione (GSH) depletion triggers APAP-induced hepatotoxicity, we investigated the role of ferroptosis in a murine model of APAP-induced acute liver failure. APAP-induced hepatotoxicity (evaluated in terms of ALT, AST, and the histopathological score), lipid peroxidation (4-HNE and MDA), and upregulation of the ferroptosis maker PTGS2 mRNA were markedly prevented by the ferroptosis-specific inhibitor ferrostatin-1 (Fer-1). Fer-1 treatment also completely prevented mortality induced by high-dose APAP. Similarly, APAP-induced hepatotoxicity and lipid peroxidation were prevented by the iron chelator deferoxamine. Using mass spectrometry, we found that lipid peroxides derived from n-6 fatty acids, mainly arachidonic acid, were elevated by APAP, and that auto-oxidation is the predominant mechanism of APAP-derived lipid oxidation. APAP-induced hepatotoxicity was also prevented by genetic inhibition of acyl-CoA synthetase long-chain family member 4 or α-tocopherol supplementation. We found that ferroptosis is responsible for APAP-induced hepatocyte cell death. Our findings provide new insights into the mechanism of APAP-induced hepatotoxicity and suggest that ferroptosis is a potential therapeutic target for APAP-induced acute liver failure.